Pattern of Nodal Metastases in Papillary Thyroid Carcinoma - Patuary, Md Khabir Uddin; Sarker, Md Zakaria; Islam, Robiul; Islam, Md Zahidul; Siddiquee, Belayat Hossain (Bangladesh Journal of Otorhinolaryngology, 2013)
Objective: The objective of this study is to determine the pattern of nodal metastases of papillary thyroid carcinoma to regional lymph in patients who have clinically positive nodes. Study design: Cross sectional study. Methods: Between January 2008 and December 2009, a total of 50 consecutive patients (15 male and 35 female) with clinical evidence of cervical lymph node metastases of papillary thyroid carcinoma was analyzed. Patients those with previous neck dissection for non thyroid malignancies and those neck node with follicular and medullary thyroid carcinoma were excluded from the study. Results: The predominant site of metastases was level III (82%), followed by level IV (62%), level II (48%), level VI (18%) and level V (16%). So, patients in the anterolateral group (level II, III and IV) were the greatest risk of metastatic disease, with level III nodes consistently the most frequently involved. No patient exhibited in level I involvement, multiple level involvement was found in 74% (37 of 50) patients. Conclusion: The high incidence of metastatic disease found in level III and IV. The level V and VI involvement were also reasonably high. Which supports the recommendation for posterolateral and anterior neck dissection for patients with papillary thyroid carcinoma with clinically positive nodes. DOI: http://dx.doi.org/10.3329/bjo.v19i1.14862 Bangladesh J Otorhinolaryngol 2013; 19(1): 46-52